miR-21-3p Regulates Influenza A Virus Replication by Targeting Histone Deacetylase-8 - Xia, Binghui; Lu, Jiansheng; Wang, Rong; Yang, Zhixin; Zhou, Xiaowei; Huang, Peitang (Frontiers in Cellular and Infection Microbiology, 2018)
Abstract Influenza A virus (IAV) is responsible for severe morbidity and mortality in animals and humans worldwide. miRNAs are a class of small noncoding single-stranded RNA molecules that can negatively regulate gene expression and play important roles in virus-host interaction. However, the roles of miRNAs in IAV infection are still not fully understood. Here, we profiled the cellular miRNAs of A549 cells infected with A/goose/Jilin/hb/2003 (H5N1) and a comparison A/Beijing/501/2009 (H1N1) strain. miRNA microarray and quantitative PCR analysis showed that several miRNAs were differentially expressed in A549 cells during IAV infection. Subsequently, we demonstrated that IAV replication was essential for the regulation of these miRNAs, and bioinformatic analysis revealed that the targets of these miRNAs affected biological processes relevant to IAV replication. Specifically, miR-21-3p was found to be down-regulated in IAV-infected A549 cells and selected for further detailed analysis. Target prediction and functional study illustrated that miR-21-3p repressed the expression of HDAC8 by targeting its 3′UTR. Furthermore, we confirmed miR-21-3p could promote virus replication, which was similar to the result of knocking down HDAC8, indicating that miR-21-3p promoted IAV replication by suppressing HDAC8 expression. Altogether, our results suggest a potential host defense against IAV through down-regulation of miR-21-3p.